Preliminary Study of NFRP-Confined Concrete for Enhancing Compressive Strength - Taufiq Saidi; Muttaqin Hasan; Zahra Amalia (Aceh International Journal of Science and Technology)
A column is a structural element that carries axial compressive loads. This compressive axial load causes the shortening of the structural column. It causes the column to be subjected to a tensile force in its axis perpendicular to the compression axis. This tensile force causes the column to collapse—reinforcement methods to improve the quality of concrete in resisting higher axial compressive loads. Strengthening the column with external restraints is expected to increase the strength of the concrete. The use of synthetic Fiber Reinforced Polymer (FRP) as a composite material for external restraint on structures is widely used for strengthening concrete structures. Considering the environmental impact, natural FRP materials have been developing nowadays. One of the natural fibers that have been researched and used as a composite material for Natural Fiber Reinforced Polymer (NFRP) is abaca fiber. This research aims to find the contribution of abaca fiber in increasing the compressive strength of confined concrete as a preliminary study. This study conducted the test by applying a compressive load to concrete specimens reinforced with NFRP restraints. Specimens were cylinders with a diameter of 150mm and 300mm in height. NFRP was applied at the cylinder circumference area (jacketing method) by using manual wet-layup techniques. The NFRP was investigated with variations in the number of NFRP layers. The results showed that NFRP-confined concrete has a higher compressive strength of 34.73% than the controlled specimen.